FUNCTIONAL ROLE OF PROPER NOUNS IN BUILDING TEXT COHESION AND COHERENCE - Qosimova Dilfuza Abdiraup qizi (Modern American Journals, 2025)
This article examines the functional role of proper nouns in ensuring text cohesion and coherence. Proper nouns, as a specific class of linguistic units, contribute not only to denoting individual entities but also to maintaining the logical and semantic unity of discourse. The study employs functional-semantic and discourse analysis methods to identify how proper names link textual elements and guide reader interpretation. Results indicate that proper nouns perform referential, cohesive, and stylistic functions, thereby strengthening text continuity and interpretative clarity.
Keywords: proper nouns, cohesion, coherence, discourse, semantics, reference, function.